α-Gal immunization positively impacts Trypanosoma cruzi colonization of heart tissue in a mouse model. - Gisele Macêdo Rodrigues da Cunha (Public Library of Science (PLoS), 2021)
Chagas disease, caused by the parasite Trypanosoma cruzi, is considered endemic in more than 20 countries but lacks both an approved vaccine and limited treatment for its chronic stage. Chronic infection is most harmful to human health because of long-term parasitic infection of the heart. Here we show that immunization with a virus-like particle vaccine displaying a high density of the immunogenic α-Gal trisaccharide (Qβ-αGal) induced several beneficial effects concerning acute and chronic T. cruzi infection in α1,3-galactosyltransferase knockout mice. Approximately 60% of these animals were protected from initial infection with high parasite loads. Vaccinated animals also produced high anti-αGal IgG antibody titers, improved IFN-γ and IL-12 cytokine production, and controlled parasitemia in the acute phase at 8 days post-infection (dpi) for the Y strain and 22 dpi for the Colombian strain. In the chronic stage of infection (36 and 190 dpi, respectively), all of the vaccinated group survived, showing significantly decreased heart inflammation and clearance of amastigote nests from the heart tissue.